Investigation and evaluation of economic variables affecting the national power of countries - Reyhaneh SalehAbadi; Mohammad Reza HafezNia; Seyyed Hadi Zarghani; syrus ahmadi (تحقیقات کاربردی علوم جغرافیایی)
The national strength of algebraic aggregation is a large number of positive and negative factors that are composed of numerous sources and resources. One of the important sources of national power in the world today and in the post-Cold War period is economic power, which is itself the bedrock of other superstructures, such as political, military, and so on. This research uses descriptive-analytical method and using library resources and field research to answer this question. What are the most important variables and indicators that shape economic power of countries? The findings of the research by examining library documents show that the four main components of economic power including infrastructure, production exchange, production level and financial resources can affect economic power. Meanwhile, 61 variables related to quadruple components were identified. Then, by using the Likert spectrum questionnaire, internal knowledge was measured to measure the importance of each of these variables. Accordingly, economic infrastructure, high-tech exports, food imports and international currency reserves were of high importance. On the other hand, variables such as the share of the poor in the consumption of national income, economic competition, foreign ownership, and commercial costs of violent crimes were of minor importance. Finally, it can be argued that countries have an obligation to take into account the factors and variables in the economic dimension to achieve their national interests and interests.